If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 6v + 7 + -2b = 1 + 5b Reorder the terms: -14 + 7 + -2b + 6v = 1 + 5b Combine like terms: -14 + 7 = -7 -7 + -2b + 6v = 1 + 5b Solving -7 + -2b + 6v = 1 + 5b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. -7 + -2b + -5b + 6v = 1 + 5b + -5b Combine like terms: -2b + -5b = -7b -7 + -7b + 6v = 1 + 5b + -5b Combine like terms: 5b + -5b = 0 -7 + -7b + 6v = 1 + 0 -7 + -7b + 6v = 1 Add '7' to each side of the equation. -7 + -7b + 7 + 6v = 1 + 7 Reorder the terms: -7 + 7 + -7b + 6v = 1 + 7 Combine like terms: -7 + 7 = 0 0 + -7b + 6v = 1 + 7 -7b + 6v = 1 + 7 Combine like terms: 1 + 7 = 8 -7b + 6v = 8 Add '-6v' to each side of the equation. -7b + 6v + -6v = 8 + -6v Combine like terms: 6v + -6v = 0 -7b + 0 = 8 + -6v -7b = 8 + -6v Divide each side by '-7'. b = -1.142857143 + 0.8571428571v Simplifying b = -1.142857143 + 0.8571428571v
| F(x)=4x^3-3x^2-8x+4 | | 4x^2+160s=-1500 | | 5-2x+7x=3-4(2-x) | | -2a+5+3a=12-21 | | 1.06=40 | | 3x-2=8x-33 | | 2h-16=-9 | | 3(x-5)(x-4)=0 | | 5c+8=5c+8 | | by-3=-6+3 | | log[4](x+14)+log[4](x+62)=5 | | 4x-2x+6=10 | | -24x-9x+3x+3=33 | | 2.7=1.3+2d | | 17+(-5m)=50+6m | | 2n=s+2u | | 3x+5x+2+x-2=180 | | 13+4b+6b+-5+-3b= | | 8+3=8x | | 36-6x=4x | | x+18=8x-7 | | 6y+5-4y=15 | | 6.8=5x+6.3 | | -10(2)(-8)=h | | 16=4+y^2+1 | | 5x+5x+2+7=5x+4+4x | | 4y-6+y+43=5y+40-3y | | 14(-5)=h | | 7x+2x=54 | | c/2/5=471/2 | | 93-16b=12 | | x^3-2x^2-49x+98=0 |